Workshop Pengenalan K3 untuk Pelajar SMK Negeri 1 Bintan Utara - Kita, Lalu Kaisar Wisnu; Diputra, Muhammad Naufal Airlangga; Hasnira, Hasnira; Mishthafiyatillah, Mishthafiyatillah; Budiarto, Arif Wahyu; Pitriani, Shelly Sri (Politeknik Negeri Batam, 2025)
Dedication to the implementation of Occupational Health and Safety (OHS) has an important urgency in ensuring a safe and healthy working environment for prospective workers. The main objective of this programme is to increase safety awareness, knowledge, and practice of OHS at the work site to reduce the risk of work-related accidents and diseases. This service programme also aims to provide workshops for prospective workers to identify, evaluate, and control OHS risks that exist in the future work environment. Education and implementation of appropriate OHS policies were used as the method of approach and are expected to create a stronger and more sustainable workplace safety culture. The results of this implementation coverage obtained an average increase of 26.3% in the Very Good category and 10.5% in the Good category. The level of awareness and OHS knowledge among workers is improved, along with the quality of the work and living environment, and the accident and injury rate is reduced. This service is expected to increase compliance with applicable OHS regulations and OHS videos, and reduce the negative impact of work accidents on worker productivity and welfare.